A review: Malay speech recognition and audio visual speech recognition - C., Y. Fook; Muthusamy, Hariharan, Dr.; Sazali, Yaacob, Prof. Dr.; Abdul Hamid, Adom, Prof. Madya. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/